2009
DOI: 10.1111/j.1742-4658.2009.07112.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel molecule 2‐[5‐(2‐chloroethyl)‐2‐acetoxy‐benzyl]‐4‐(2‐chloroethyl)‐phenyl acetate inhibits phosphoinositide 3‐kinase/Akt/mammalian target of rapamycin signalling through JNK activation in cancer cells

Abstract: Screening a compound library of compound 48/80 analogues, we identified 2‐[5‐(2‐chloroethyl)‐2‐acetoxy‐benzyl]‐4‐(2‐chloroethyl)‐phenyl acetate (E1) as a novel inhibitor of the phosphoinositide 3‐kinase/Akt pathway. In order to determine the mechanism of action of E1, we analysed the effect of E1 on components of the phosphoinositide 3‐kinase/Akt/mammalian target of rapamycin (mTOR) pathway. E1 demonstrated dose‐dependent and time‐dependent repression of Akt and mTOR activity in prostate and breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, JNK1/2 activation Cell lysates were then prepared, and the expression of a JNK1/2 and pJNK1/2, b p38 and pp38, c AKT and pAKT, d GSK-3β and pGSK-3β, e β-catenin and f EGFR were examined using Western immunoblotting. Bars represent the mean ± SEM from 4 independent experiments Representative blots are shown above each bar graph repressed Akt activity in MCF-7 cells [52]. Recent studies have also suggested that a decrease in the level of Akt could lead to higher activity of p38 MAPK [53].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, JNK1/2 activation Cell lysates were then prepared, and the expression of a JNK1/2 and pJNK1/2, b p38 and pp38, c AKT and pAKT, d GSK-3β and pGSK-3β, e β-catenin and f EGFR were examined using Western immunoblotting. Bars represent the mean ± SEM from 4 independent experiments Representative blots are shown above each bar graph repressed Akt activity in MCF-7 cells [52]. Recent studies have also suggested that a decrease in the level of Akt could lead to higher activity of p38 MAPK [53].…”
Section: Discussionmentioning
confidence: 96%
“…Western blotting was performed on whole-cell extracts by lysing cells in SDS/PAGE buffer as previously described 17. Antibodies to Ki67 (MIB-1; Dako), ER (sc543; Santa Cruz Biotechnology, Dallas, Texas, USA), p21 (CP36, CP74; Millipore, Billerica, Massachusetts, USA) and α-tubulin (B-5-1-2; Sigma-Aldrich) were used at a dilution of 1:1000.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed on whole-cell extracts by lysing cells in SDS/PAGE buffer as previously described ( Ho et al , 2009 ). Antibodies to FOXA1 (ab23738, Abcam), α -tubulin (B-5-1-2, Sigma-Aldrich, Tokyo, Japan), ER (sc543, Santa Cruz Biotechnology), PR (clone 16, Leica, Milton Keynes, UK), and CK5/6 (D5/16 B4, Dako) were used.…”
Section: Methodsmentioning
confidence: 99%